EUROPEAN UNION POLICY ON CREATIVE INDUSTRIES: PUBLIC ADMINISTRATION CHALLENGES AND PROSPECTS FOR UKRAINE - Fedoriv, Svyatoslav; Pozniakova, Olena (Public Management and Policy, 2025)
Cultural and creative industries (CCIs) represent one of the most dynamic sectors of the modern economy, combining cultural value, innovative potential, and capacity for social transformation. The European Union’s policy framework considers CCIs a strategic resource for sustainable development, digital transformation, and inclusive growth. Given Ukraine’s status as a candidate for EU membership, analyzing European approaches to supporting CCIs is crucial for adapting effective models of public administration to national realities. The study of the division of competences between EU institutions and Member States in the cultural sphere is particularly important, as it defines the Union’s supporting role and the autonomy of states in implementing national cultural strategies. The article examines the legal foundations of the EU’s cultural policy as defined by the Treaty on the Functioning of the European Union (TFEU), which classifies culture as a shared but primarily supporting competence. The roles of key EU institutions in shaping CCI policy are analyzed: the European Commission designs strategic documents and manages support programs; the European Parliament adopts resolutions, approves budgets, and exercises oversight; and the Council of the EU coordinates cultural policy through its Education, Youth, Culture and Sport configuration and Work Plans for Culture. Major support programs such as Creative Europe, Horizon Europe, Erasmus+, InvestEU, ESF+, and Interreg are discussed, highlighting their priorities, instruments, and budgetary allocations. The article also explores Ukraine’s participation in Creative Europe as an associated member, including the expansion of access to the MEDIA strand after 2022. EU policy on CCIs illustrates a model of multilevel governance combining strategic guidance from EU institutions with the autonomy of Member States. The division of competences ensures that while the EU does not directly harmonize national cultural policies, it plays a key role in coordinating efforts, providing financial support, and promoting best practices. For Ukraine, leveraging these mechanisms is essential for building sustainable institutional support for CCIs, integrating into the European cultural space, and improving the effectiveness of public administration in this field. The EU experience demonstrates that CCIs can become a powerful tool for economic recovery, inclusion, and international cooperation.